Efeitos de sistemas de manejo pré-semeadura da soja sobre a dinâmica no solo e eficácia de herbicidas - Macedo, Gabrielle de Castro [UNESP] (2015)
The presence of straw on the soil surface can alter the population dynamics of weeds present in the area, and influence the behavior of herbicides in soil. Currently, little is known about the dynamics of release of herbicides with residual effect when your application is performed on the green coverage in the management of pre-sowing soybean, but it is assumed that the distribution and dynamics are altered. This study aimed to evaluate the behavior in soil, the efficiency in weed control and selectivity to the culture of sulfentrazone and flumioxazin herbicide when applied over two types of covers in different desiccation management systems in pre-sowing soybean. There were two experiments, in Botucatu, São Paulo, in areas with millet and sorghum coverage, in a randomized block design with 7 treatments and 4 replications. The treatments were a combination of herbicides in different management systems of coverage crops, which are: glyphosate (720 g e.a. ha-1) 20 days before sowing (DBS) + sulfentrazone (600 g i.a. ha-1) 10 DBS; glyphosate (720 g e.a. ha-1) 20 DBS + flumioxazin (50 g i.a. ha-1) 10 DBS; glyphosate (720 g e.a. ha-1) + sulfentrazone (600 g i.a. ha-1) 10 DBS; glyphosate (720 g e.a. ha-1) + flumioxazin (50 g i.a. ha-1) 10 DBS; sulfentrazone (600 g i.a. ha-1) 10 DBS without the presence of coverage; flumioxazin (50 g i.a. ha-1) 10 DBS without the presence of cover and a control with application of glyphosate (720 g e.a. ha-1) 10 DBS. Were evaluated the availability of herbicides in the soil through periodic collections, weed control, weed survey, selectivity of herbicides to the crop, production and soybean yield components. For quantification of herbicides used a LCMS-MS system consisting of a High Performance Liquid Chromatography (HPLC) coupled with mass spectrometry. For flumioxazin, amounts of herbicide present in the samples were below the detection limit of the analytical method ...